2001
DOI: 10.1093/humrep/16.3.584
|View full text |Cite
|
Sign up to set email alerts
|

Cervical ectopic twin pregnancy: diagnosis and conservative treatment: Case report

Abstract: A case of cervical ectopic twin pregnancy with cardiac activity in both embryos is presented. It was diagnosed in the eighth week of gestation by ultrasonography, and treated conservatively with intra-amniotic administration of methotrexate under ultrasonographic guidance followed by curettage. This procedure allows subsequent gestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
1
23
0
4
Order By: Relevance
“…with fetal cardiac activity at presentation): a median of 129 days compared with a median of 43 days. The median number of blood tests to measure serum hCG for each woman was 12 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and the median number of scans during the period of follow-up was 4 (range, 2-8).…”
Section: Resultsmentioning
confidence: 99%
“…with fetal cardiac activity at presentation): a median of 129 days compared with a median of 43 days. The median number of blood tests to measure serum hCG for each woman was 12 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] and the median number of scans during the period of follow-up was 4 (range, 2-8).…”
Section: Resultsmentioning
confidence: 99%
“…Another even more complex case was that of cervical ectopic pregnancy with placenta accrete with bladder involvement. There have also been reported cases of cervical ectopic twin pregnancy [23], etc.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported medications are MTX and KCl. 13,21,27,35,41,44,46,51 Administration of intraamniotic prostaglandins F2α have also been described by Spitzer et al and Vega et al 59,60 Mefiprestone administered along with MTX to induce feticide has been reported by Pathak et al and Shreshta et al 43,48 In the presence of progesterone, mifepristone acts as a competitive receptor antagonist at the progesterone receptor. Mifepristone induces decidual breakdown indirectly, leading to trophoblast detachment and resulting in decreased syncytiotrophoblast production of HCG, which in turn causes decreased production of progesterone by the corpus luteum.…”
Section: Medical Therapymentioning
confidence: 91%
“…Direct injection into the conceptus has also been investigated. 13,27,35,40,41,51 Because the use of methotrexate in CEP is relatively new, a standardized protocol is not yet available, even for tubal pregnancy. (MTX -methotrexate, FHR-fetal heart rate, UAE-uterine artery embolization, N-number, HCG -human chorionic gonadotropin)…”
Section: Medical Therapymentioning
confidence: 99%